Slovenija - Jogan, Maca (Družboslovne razprave, 2015)
In Slovenia, the shaping of an autonomous state also meant replacing the socialist system with a capitalist one. The article presents the Slovenian population's changing evaluation of these two systems based on data collected through the Slovenian public opinion survey from 1990 to 2013. The analysis considers general assessments regarding: a) the socialist period in general and by time sequences; b) the quality of life before and after establishing the independent state; c) the relationship to the notions of Europe, socialism and capitalism, which are complemented by the respondents' statements on how four selected notions (justice, humanity, inequality and well-being) correspond to their images in both systems.
Keywords: Anticommunism; Antikomunizem; Democracy; Demokracija; Capitalism; Kapitalizem; Social inequality; Družbena neenakost; Socialism; Socializem; Slovenia; Slovenija